Warfarin usage among elderly atrial fibrillation patients with traumatic injury, an analysis of United States Medicare fee‐for‐service enrollees. (11th August 2014) - Liu, Xinggang; Baumgarten, Mona; Smith, Gordon; Gambert, Steven; Gottlieb, Stephen; Rattinger, Gail; Albrecht, Jennifer; Langenberg, Patricia; Zuckerman, Ilene
Abstract This study examined warfarin usage for elderly Medicare beneficiaries with atrial fibrillation (AF) who suffered traumatic brain injury (TBI), hip fracture, or torso injuries. Using the 5% Chronic Condition Data Warehouse administrative claims data, this study included fee‐for‐service Medicare beneficiaries who had a single injury hospitalization (TBI, hip fracture, or major torso injury) between 1/1/2007 and 12/31/2009, with complete Medicare Parts A, B (no Medicare Advantage), and D coverage 6 months before injury, and who were aged 66 years or older and diagnosed with AF at least 1 year before injury. About 45% of the AF patients were using warfarin before TBI or torso injury, and 35% before hip fracture. After injury, there was a dramatic and persistent decrease in warfarin use in TBI and torso injury groups (30% for TBI and 37% for torso injury at 12 months after injury). Warfarin usage in hip fracture patients also dropped after injury but returned to pre‐injury level within 4 months. TBI and torso injury lead to significant decreases in warfarin usage in elderly AF patients. Further research is needed to understand reasons for the pattern and to develop evidence‐based management strategies in the post‐acute setting.